Flowable placental connective tissue matrices for tendon repair: A review - Nicole M Protzman; Yong Mao; Raja Sivalenka; Desiree Long; Anna Gosiewska; Robert J Hariri; Stephen A Brigido (Journal of Biology and Medicine - Peertechz Publications, 2022)
Tendon injuries are associated with considerable pain and disability. Owing to the hypovascularity and hypocellularity of the tissue, natural tendon healing is slow and ineffective. Traditional conservative and surgical treatment options fail to address the underlying pathology. As a result, the healed tendon is mechanically incompetent and prone to degeneration and rupture. Therefore, new biological methods have been suggested to enhance tendon repair and regeneration. Flowable Placental Connective Tissue Matrices (FP-CTMs) represent a promising means to promote tendon healing. Like non-flowable placental scaffolds, FP-CTMs possess the innate healing properties of the placenta and provide structural and biochemical extracellular matrix components. Unlike their non-flowable counterparts, FP-CTMs have the added benefits of minimal invasiveness and the capacity to fill irregular spaces. FP-CTMs can enhance tendon repair by providing a three-dimensional extracellular matrix for cellular attachment and proliferation while decreasing inflammation and limiting adhesion formation. The present report reviews tendon biology, pathology, healing, and current treatment modalities, followed by a comprehensive literature review, evaluating the clinical application of FP-CTMs for tendon repair. Recent research suggests that the use of FP-CTMs in tendon repair is safe and efficacious and further indicates that FP-CTMs can modulate the tendon repair environment and improve clinical outcomes. However, the existing clinical evidence is limited to retrospective case series with no control group. Therefore, additional work must be performed to better understand the clinical applications and therapeutic benefits of FP-CTM in tendon repair compared with conventional treatments.